PENGGUNAAN MODEL PROBLEM BASED INSTRUCTION (PBI) DALAM UPAYA MENINGKATKAN KEMANDIRIAN BELAJAR BIOLOGI PADA SISWA KELAS III C SMPN 16 BANDAR LAMPUNG TAHUN PELAJARAN 2004/2005 - JAMLO, TRI; PURWADI, PURWADI (Prodi Pendidikan Biologi FKIP UNS, 2005)
This is collaborative action research wich carried out toward student of SMP Nergeri 16 Bandar Lampung. The aim of this research was enhancing the self learning motivation by using Problem Based Intruction (PBI) model. The research conducted in 2 cycles, using the criteria of teacher?s performance and student?s ability toward biological learning. The data awas then analized and interpreted to show the improving teacher performance for each cycle. The result showed that the teacher was a good fascilitator (score 2,98 in cycle 1 and 2,93 in cycle), so it?s able to enchace the self learning motivation of student, indicated with the increasing point of the readiness of study, the higly motivated in answer and question interaction, ability in answering the questions, giving opinion, creative, and highly initiative to study. That self learning motivation then gives rise to the average class mark even its equitability thus showed the better teaching and learning processes. Key Words : Problem Based Intruction (PBI), Self Learning motivation